Design, rationale and initial findings from HERA‐FIB on 10 222 patients with atrial fibrillation presenting to an emergency department over an 11‐year period - Salbach, Christian; Yildirim, Mustafa; Hund, Hauke; Biener, Moritz; Müller-Hennessen, Matthias; Frey, Norbert; Katus, Hugo; Giannitsis, Evangelos; Milles, Barbara Ruth (Journal of the American Heart Association, 2024)
For the majority of patients with atrial fibrillation (AF), disease management has improved in recent years. However, there are still populations underrepresented or excluded in current registries and randomized controlled trials. HERA‐FIB (Heidelberg Registry of Atrial Fibrillation) was planned to assess real‐world evidence for the prevalence, demographic characteristics and management of patients with the diagnosis of AF presenting consecutively to a chest pain unit.Methods and ResultsHERA‐FIB is a retrospective, observational, single‐center study on patients with a diagnosis of AF presenting to a chest pain unit from June 2009 until March 2020. This article describes the structure, governance, outcome assessment, quality and data collection processes of the registry. Additionally, characteristics of populations of special interest are described. The study consecutively enrolled 10 222 patients presenting with AF to the chest pain unit of the University Hospital of Heidelberg. Clinical parameters and patient characteristics were assessed retrospectively. Outcome parameters included rates for all‐cause death, stroke, myocardial infarction and major bleedings. We were able to investigate patient cohorts of special interest such as advanced chronic kidney disease, octogenarians, and those with acute coronary syndrome who are often underrepresented in current studies and randomized controlled trials.ConclusionsHERA‐FIB is one of the largest real‐world single‐center retrospective registries on patients with AF, which captures the era of transition from vitamin K antagonists to non-vitamin K oral anticoagulation regimens in clinical practice and offers the possibility to investigate patient populations usually underrepresented or excluded in current available randomized controlled trials and registries. Registration URL: https://www.clinicaltrials.gov; unique identifier: NCT05995561.
Gesehen am 30.09.2024